Addition to Sweden’s freshwater sponge fauna and a phylogeographic study of Spongilla lacustris (Spongillida, Porifera) in southern Sweden - Robert, Chloé; Pereira, Raquel; Thollesson, Mikael (European Journal of Taxonomy, 2022)
Freshwater sponges constitute an overlooked part of the freshwater fauna in Sweden and there has been no recent systematic survey. Hitherto three species have been found in Sweden: Spongilla lacustris (Linnaeus, 1759), Ephydatia fluviatilis (Linnaeus, 1759) and E. muelleri (Lieberkühn, 1856). Neighbouring countries (Norway, Denmark, Estonia) harbour at least one additional species. We present a study on freshwater sponge diversity and distribution in the southern half of Sweden. We hypothesized dispersal within catchments to be less constrained than between, even at shorter intercatchment than intracatchment distances, and, as result, genetic distances being greater between than within catchments. We collected and identified freshwater sponges from 34 sites, using morphological and molecular data (coxI, 28S rRNA gene). We can report the presence of Eunapius fragilis (Leidy, 1851) in Sweden for the first time, and that S. lacustris is the most abundant and widely distributed freshwater sponge in Sweden. Genetic markers were tested on S. lacustris individuals for a phylogeographic study. From the 47 primers (24 markers), one pair presented successful amplification and enough variation for phylogeographic studies – i56, an intron located in a conserved gene. Seven different variants were found in the sampling area, but no clear population structure was observed.